2014
DOI: 10.1007/s00586-014-3547-9
|View full text |Cite
|
Sign up to set email alerts
|

Sacroiliac joint syndrome 10 years after lumbar arthroplasty: the importance of spinopelvic alignment

Abstract: The low rate of SIJD 10 years after lumbar arthroplasty might be explained by the preservation of the spinopelvic balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…38 Several authors have examined lumbar sagittal balance as a contributor to post-lumbar fusion SIJ pain suggesting that failure to restore lumbar lordosis (leaving the patient with a residual pelvic incidence-lumbar lordosis mismatch) is associated with post-lumbar fusion SIJ pain. [39][40][41]…”
Section: Sij Pain Etiology and Epidemiologymentioning
confidence: 99%
“…38 Several authors have examined lumbar sagittal balance as a contributor to post-lumbar fusion SIJ pain suggesting that failure to restore lumbar lordosis (leaving the patient with a residual pelvic incidence-lumbar lordosis mismatch) is associated with post-lumbar fusion SIJ pain. [39][40][41]…”
Section: Sij Pain Etiology and Epidemiologymentioning
confidence: 99%
“…In one study, David [100] concluded that the "rate of reoperation secondary to adjacent segment disease is ten times lower than the rates reported in the literature for fusion." Furthermore, the rates of secondary sacroiliac joint dysfunction following LDA were low in the mid-term [101]. Studies of modern LDAs have also reported faster patient recovery, higher satisfaction in the short-term compared to the fusion techniques [95].…”
Section: Operative Treatmentmentioning
confidence: 99%